When Job Dissatisfaction Leads to Creativity: Encouraging the Expression of Voice - Zhou, Jing; George, Jennifer M. (Academy of Management Journal, 2001)
This study focused on the conditions under which job dissatisfaction will lead to creativity as an expression of voice. We theorized that useful feedback from coworkers, coworker helping and support, and perceived organizational support for creativity would each interact with job dissatisfaction and continuance commitment (commitment motivated by necessity) to result in creativity. In a sample of 149 employees, as hypothesized, employees with high job dissatisfaction exhibited the highest creativity when continuance commitment was high and when (1) useful feedback from coworkers, or (2) coworker helping and support, or (3) perceived organizational support for creativity was high.